2011
DOI: 10.1002/eat.20954
|View full text |Cite
|
Sign up to set email alerts
|

A case of anorexia nervosa with disseminated intravascular coagulation syndrome

Abstract: A 36-year-old Japanese woman with anorexia nervosa (AN) was admitted to our department because of severe emaciation. Although we were thorough in her clinical management and were careful to avoid precipitating refeeding syndrome, disseminated intravascular coagulation (DIC) developed 3 weeks after hospitalization. We treated her for DIC with sepsis using anticoagulants, protease inhibitors, antithrombin, and platelet concentrate transfusion. To treat her bacterial infection, we administered antimicrobial drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Furthermore, the possibility of damage to the intestinal barrier, as indicated by the low serum DAO activity levels, might reflect increased risk of bacterial translocation 14 in AN patients with severe malnutrition. 3 Usami et al 15 reported that bacterial translocation occurs more readily when DAO activity is low. Thus, the measurement of serum DAO activity levels might be useful for evaluating risk of bacterial translocation in AN patients with severe malnutrition.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Furthermore, the possibility of damage to the intestinal barrier, as indicated by the low serum DAO activity levels, might reflect increased risk of bacterial translocation 14 in AN patients with severe malnutrition. 3 Usami et al 15 reported that bacterial translocation occurs more readily when DAO activity is low. Thus, the measurement of serum DAO activity levels might be useful for evaluating risk of bacterial translocation in AN patients with severe malnutrition.…”
Section: Discussionmentioning
confidence: 85%
“…3 Usami et al 15 reported that bacterial translocation occurs more readily when DAO activity is low. 3 Usami et al 15 reported that bacterial translocation occurs more readily when DAO activity is low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No suicide cases were identified in our study, which was probably because the population included inpatients only. Few studies have suggested the possibility of sepsis-induced death in ED patients [16,17]. Furthermore, a previous review indicated that IVH was not associated with an increase in sepsis compared with EN [18].…”
Section: Discussionmentioning
confidence: 99%